Sensitivity and specificity of a rapid point-of-care test for active yaws: a comparative study - Telek Ayove, BSc; Wendy Houniei, HEO; Regina Wangnapi, MBBS; Sibauk V Bieb, MBBS; Walter Kazadi, MD; Lisol-Nirau Luke, BSc; Clement Manineng, MBBS; Penias Moses, HEO; Raymond Paru, BSc; Javan Esfandiari, MSc; Prof. Pedro L Alonso, MD; Elisa de Lazzari, MSc; et al. (Elsevier, 2014)
Background: To eradicate yaws, national control programmes use the Morges strategy (initial mass treatment and biannual resurveys). The resurvey component is designed to actively detect and treat remaining yaws cases and is initiated on the basis of laboratory-supported reactive non-treponemal serology (using the rapid plasma reagin [RPR] test). Unfortunately, the RPR test is available rarely in yaws-endemic areas. We sought to assess a new point-of-care assay-the Dual Path Platform (DPP) syphilis assay, which is based on simultaneous detection of antibodies to treponemal and non-treponemal antigens-for guiding use of antibiotics for yaws eradication. A secondary goal was to ascertain at what timepoint the DPP assay line reverted to negative after treatment. Methods: 703 children (aged 1-18 years) with suspected clinical yaws living in two remote, yaws-endemic villages in Papua New Guinea were enrolled. Clinical suspicion of yaws was established according to a WHO pictorial guide. We obtained blood samples from all patients. We calculated the sensitivity and specificity of the DPP assay for detection of antibodies to treponemal (T1) and non-treponemal (T2) antigens and compared values against those obtained with standard laboratory tests (the Treponema pallidum haemagglutination assay [TPHA] and the RPR test). We followed up a subsample of children with dually positive serology (T1 and T2) to monitor changes in DPP optical density (using an automatic reader) at 3 and 6 months. This trial is registered with ClinicalTrials.gov, number NCT01841203. Findings: Of 703 participants, 389 (55%) were reactive for TPHA, 305 (43%) for the RPR test, and 287 (41%) for both TPHA and the RPR test. The DPP T1 (treponemal) assay had a sensitivity of 88·4% (95% CI 84·8-91·4) and specificity of 95·2% (92·2-97·3). The DPP T2 (non-treponemal) assay had a sensitivity of 87·9% (83·7-91·3) and specificity of 92·5% (89·4-94·9). In subgroup analyses, sensitivities and specificities did not differ according to type of specimen (plasma vs whole blood). For specimens with an RPR titre of 1:8 or greater, the sensitivity of the DPP T2 assay was 94·1% (95% CI 89·9-96·9). Serological cure (including seroreversion or a fourfold reduction in optical density value) was attained at 6 months in 173 (95%) of 182 children with dual-positive serology. Interpretation: The DPP assay is accurate for identification of antibodies to treponemal and non-treponemal antigens in patients with yaws and avoids the need for laboratory support. A change of diagnostic procedure from the currently implemented RPR test to the simpler DPP assay could ease the implementation of yaws eradication activities. Funding: Chembio Diagnostic Systems, Newcrest Mining, and the Papua New Guinea National Department of Health.